Effect of mineral-phytobiotic supplement on mass growth and meat productivity of crossbred sheep - M. D. Perih (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки, 2023)
The article presents data on the effect of a mineral-phytobiotic supplement on the age dynamics of the live weight of sheep obtained from crossbred ewes. The age dynamics of absolute, relative, and average daily growth rates were analyzed. The results of slaughter and the morphological composition of carcasses of 5-month-old lambs were studied. As a result of the research, it was found that in the first 2 months after birth, the mass of the lambs was higher by 12.5 %, and in lambs by 18.65 %, which was 15.58 % on average. In the following age periods, the live weight of gilts and lambs of the experimental group was also higher than the sheep of the control group by 17.68, respectively; 20.64; 12.45 and 17.08 %, while in the lambs of the experimental group, the intensity of increase compared to the control group was slightly lower and amounted to 14.92, respectively; 14.22; 12.89 and 9.56 %. The highest average daily growth in both groups of experimental sheep was in the period from birth to 2 months of age. By the age of 6 months, lambs and gilts of both groups had a live weight higher than 50 % compared to 18-month-old sheep. The slowdown in absolute growth is observed starting from 49 months of age, which in our opinion is related to weaning and transition to pasture. According to the results of the slaughter of 5-month-old lambs, it was established that the weight of the cartridge carcass, the slaughter weight, and the slaughter yield of the sheep of the experimental group was higher by 26.58, respectively; 22.75 and 7.89 %. The morphological composition of the carcasses of the 5-month-old lambs of the experimental group was higher by 32.69 and 22.26 %, respectively, in terms of pulp yield and fleshiness ratio.